The Decrease Of Nitrate and Phosphate On Tofu Liquid Waste By Combined Biofilter and Eichhornia crassipes (Mart) Solms For Fish Life Media - Esti Mardiana; Eko Purwanto; Budijono ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted from September-December 2013 in the tofu factory which is located on Kubang Raya street, Tarai Bangun village, Kampar distric, Riau province. The purpose of this research is the aims is to know the decrease of nitrate and phosphate in tofu liquid waste. The research used anaerob and aerob reactor as treatmen and without media as control. Results of combination treatment anaerobic - aerobic reactor biofilter with Eichhornia crassipes (Mart) Solms) of media can reduce nitrate levels during the observation of the effectiveness reaches 40,0-74.2 % and phosphate can be dropped with 46,2-72.3% effectiveness. For other parameters also are in accordance with the quality standards that have been established, such as pH 7, temperature 28 0C, and DO of 3.76 mg / l. While the media processing unit without (control) can also reduce levels of nitrate and phosphate, but the effectiveness of processing lower when compared to the unit of media. Where the effectiveness of 15,1-21.8 % for nitrate and phosphate effectiveness decline to reach 16,1-26.6%. processed of tofu wastewater is feasible to use for live media Sepat rawa (Trichogaster trichopterus) and Nila (Oreochromis niloticus) except Pantau janggut (Esomus sp). This is evidenced by the survival of Sepat rawa reaches 86.67 %, Nila 70%, and Pantau janggut only reached 46.67 % during 2 weeks of testing.Keywords : Nitrates, Phosphates, waste water, biofilter, plastic bottle, Water hyacinth